Penerapan Keselamatan Dan Kesehatan Kerja (K3) Di Daya Tarik Wisata Bounce Bali Desa Canggu Kecamatan Kuta Utara Kabupaten Badung - Kurniawan, Abel; Sukana, Made (JURNAL DESTINASI PARIWISATA, 2019)
Bounce Bali is one of the tourist attraction in Bali. It is located in Canggu Village, Kuta Utara District, Badung Regency. It offers an indoor trampoline activity. This sport has a potential risk. Therefore, it is essential to implement safety and healthy procedure. The types of data are qualitative. This research analyzes the primary and secondary source of data. Data are collected through an observation, interview, and literature review. They are discussed descriptively. Qualitative data analyzes are carried out to understand the aim of the research. The result of the study shows that Bounce Bali has been applied the safety and heathy procedure. They implement the standards of using the trampoline and provide the first aid facility. Keywords: Trampoline Tourist Attraction, Safety and Healthy Procedure, Bounce Bali